The hollow : a Hercule Poirot novel - Christie, Agatha, 1890-1976. (New York : Berkley Books, 1984)
Belgian detective Hercule Poirot sets out to investigate a baffling case when he arrives at Lady Angkatell's estate for a weekend house party to find a doctor lying dead in a puddle of blood and his timid wife standing over the corpse with a gun.
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction